Grace [videorecording (DVD)] - Lawrence, Sharon, 1961-; Marks, Annika; Mowen, Chase ([Publisher not identified], 2015)
A typical weekend of binge drinking in a small Florida town lands Grace Turner in the county jail. Forced to embark on a new path, she decides to go to AA and put the pieces of her shattered life back together.